COMPUTATIONAL DRUG DISCOVERY OF POTENT ANTIMALARIAL XANTHONES: A SYSTEMATIC REVIEW AND ADMET-GUIDED IDENTIFICATION OF A LEAD CANDIDATE - Joanne Theophilia Winata; Komang Dian Aditya Putra; Yosi Bayu Murti; Akhmad Kharis Nugroho (Journal Pharmaceutical Science and Application, 2025)
Background: Artemisinin resistance mediated by Kelch13 mutations threatens malaria elimination efforts. Xanthones from Garcinia mangostana present a promising alternative scaffold for antimalarial drug development. Objective: This study systematically identified potent xanthones reported in the literature and evaluated their pharmacological potential using computational methods. Methods: A comprehensive systematic review was conducted across PubMed, Scopus, and Wiley Online Library (through September 2025) following PRISMA 2020 guidelines, searching for "Xanthone" combined with "Antimalarial" or "Plasmodium". Selection criteria included original research reporting IC50 values against Plasmodium falciparum. Results: Among 165 identified compounds from 46 studies, 18 demonstrated potent activity (IC50 < 1 µM). Structure-Activity Relationship analysis revealed that synthetic xanthones with alkylamino side chains were substantially more efficacious than natural isolates. Compound 117 (3-(3- (dimethylamino)propoxy)-6,8-dihydroxy-2-methoxy-7-(3-methylbut-2-en-1-yl)-9H-xanthen-9- one) emerged as the lead candidate with IC50 of 0.1 µM. In silico ADMET profiling predicted superior intestinal absorption (>90%), compliance with Lipinski's Rule, and a favourable-toxicity profile (non-mutagenic, non-hepatotoxic) compared to the natural prototype α-mangostin. Conclusion: This integrated systematic review-cheminformatics approach, strengthened by transparent multi-criteria prioritization, identified Compound 117 as a promising pre-clinical candidate requiring further biological evaluation, including in vivo efficacy in rodent malaria models, in vitro cytotoxicity profiling, and experimental validation of predicted CYP interactions before advancing toward clinical translation.